2017
DOI: 10.18203/2394-6040.ijcmph20170260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cold chain and logistics management practice in Durg district of Chhattisgarh: pointer from Central India

Abstract: Background: Immunization is the effective method of preventing childhood diseases. One of the important elements for improving the immunization is cold chain and vaccine logistics management which are the left and right hands of immunization programme. Keeping this in mind, the present study was done with the objectives a) to ascertain the status of cold chain equipment and logistics management using GOI monitoring format and b) to ascertain the awareness and practice of cold chain handlers about cold chain eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 5 publications
1
30
7
2
Order By: Relevance
“…(Table 5). 8 The present study stated that, all CCPs (100%) had separate temperature log book for ILR and DF in comparison to study done by Sinha et al observed only at 45% centers. 8 In similar study done by Rao et al observed at 94.2% centers.…”
Section: Methodscontrasting
confidence: 47%
See 1 more Smart Citation
“…(Table 5). 8 The present study stated that, all CCPs (100%) had separate temperature log book for ILR and DF in comparison to study done by Sinha et al observed only at 45% centers. 8 In similar study done by Rao et al observed at 94.2% centers.…”
Section: Methodscontrasting
confidence: 47%
“…8 The present study stated that, all CCPs (100%) had separate temperature log book for ILR and DF in comparison to study done by Sinha et al observed only at 45% centers. 8 In similar study done by Rao et al observed at 94.2% centers. 9 The findings in our study was more than that what Mallik et al (60%), Samath et al (65%) and Sachdeva et al (71.87%) found in their studies.…”
Section: Methodscontrasting
confidence: 47%
“…[12] Sinha et al in their study found that in 85% ILRs T-series and hepatitis B vaccine were stored in top of ILRs. [13] Similarly, Rao et al in their study done at Primary Health Care Centres in South India found improper storage of vaccine in 10% of study centers. [14] In other studies done in various areas of Gujarat state, similar findings were reported by Sharma et al (90%) and Tushar et al (93.2%) that vaccines were properly arranged in the ILR.…”
Section: Resultsmentioning
confidence: 85%
“…In a similar study Sinha et al reported that among all CCPs visited only 40% had dedicated space/room and 75% had dedicated space for syringes and diluents. 9 Ice packs are key components of cold chain, used for inside lining of cold boxes and vaccine carrier at facility and at field respectively for vaccine storage and transport. The water should be filled only up to the level of mark on the side and cork should be tight so that there is no leakage.…”
Section: Discussionmentioning
confidence: 99%
“…8 Success of national immunization program is highly dependent on supply chain system for delivery of vaccines and cold chain equipments. 9 Immunization against a disease is achieved only if a potent vaccine is administered. The system of transporting, storing and distributing vaccines in a potent state at the recommended temperature from the point of manufacture to the point of use is the cold chain.…”
Section: Introductionmentioning
confidence: 99%